Twenty-Eight-Day Fasting, Lunar Visibility, and Communal Eid Observance in Islamic Jurisprudence - Rizal Mananu; Jusmaliah; Nurul Ilmah; Syamsul Bakri (Cv. Kalimasada Group, 2026)
The determination of Ramadan and Eid al-Fiṭr becomes legally complex when Muslims travel between countries that begin or end the month on different dates. This study examines the jurisprudential problem of a traveler who completes only twenty-eight days of fasting before joining Eid in a destination country, asking whether such fasting constitutes a complete Ramadan and whether qaḍāʾ is required. Using a qualitative normative-juridical method, it analyses Qurʾānic and prophetic foundations on fasting, crescent sighting, and lunar-month completion, together with fiqh doctrines such as ruʾyat al-hilāl, ikhtilāf al-maṭāliʿ, communal authority, traveler concessions, and qaḍāʾ. Comparative fiqh reasoning and hypothetical travel cases evaluate twenty-eight-day and thirty-one-day scenarios. The findings show that Islamic law recognises Ramadan as a lunar month of twenty-nine or thirty days; therefore, twenty-eight fasts do not constitute a complete Ramadan. A traveler present where Eid has been officially or communally declared should join the host community to preserve public religious unity, yet this does not remove the individual obligation to complete the missing day through qaḍāʾ. The study positions qaḍāʾ as the mechanism mediating communal conformity and individual ritual completeness, contributing to legal discourse on transnational mobility, lunar visibility, and public religious authority within a living-law and legal-pluralism framework relevant to Indonesia.